Early development of turn-taking in vocal interaction between mothers and infants - Gratier, Maya; Devouche, Emmanuel; GUELLAI, Bahia; Infanti, Rubia; Yilmaz, Ebru; Parlato, Erika (Frontiers in Psychology, 2015)
Infants are known to engage in conversation-like exchanges from the end of the second month after birth. These ‘protoconversations’ involve both turn-taking and overlapping vocalization. Previous research has shown that the temporal organization of adult-infant turn-taking sequences is similar to that of adult verbal conversation. It has also been shown that young infants adjust the quality of their vocalization in response to the quality and timing of adult vocalization. We present new evidence of turn-taking interaction in infants aged between 8 and 21 weeks based on the analysis of 176 samples of naturalistic face-to-face interactions from 51 dyads. We found high levels of latched turns as well as frequent initiation of turn-taking by infants at these ages. Our data do not support the hypothesis that turn-taking ability increases with age between 2 and 5 months but do suggest that infants are active participants in turn-taking from the earliest age and that mothers adjust turn-taking formats to infants.